Evaluation of a multiobjective performance index for distribution systems with distributed generation - Ochoa, Luis F. [UNESP]; Padilha-Feltrin, Antonio [UNESP]; Harrison, Gareth P. (My University, 2005)
Here a multiobjective performance index for distribution systems with distributed generation based on a steady-state analysis of the network is proposed. This index quantifies the distributed generation impact on total losses, voltage profile and short circuit currents, and will be used as objective function in an evolutionary algorithm aimed at searching the best points for connecting distributed generators. Moreover, a loss allocation technique, based on the Zbus method, is applied on the original configuration of the network to obtain a good quality initial population. An IEEE medium voltage distribution network is analysed and results are presented and discussed.
Keywords: Electric losses; Electric potential; Electric power generation; Evolutionary algorithms; Short circuit currents; Multiobjective performance index; Steady-state analysis; Voltage profiles; Electric power distribution